Academic Senate Minutes 2019-01-31 - Academic Senate:::::::::
Agenda approved. Minutes of 4/18 amended and approved. Chair Report. Provost Report. Statewide Senator Report. Senate Budget Subcommittee Report. Structure and Functions Self – Study Report. Chair-Elect Report. Resolution in Support of War and Peace Lecture Series approved for Senate agenda. Vice President of Administration and Finance Report. Resolution in Support of a Gender and Sexuality Coordinator approved for Senate agenda. Chief Student Affairs Officer Report. APC Report. SAC Report. CFA Report. Return to Vice Chair Report. Associated Students Report. Sustainability Executive Committee Report. Return to SAC Report. Senate Agenda approved.